THE WIKE PHENOMENON, POLITICAL DUALISM AND TRANS-PARTISAN HEGEMONY IN CONTEMPORARY NIGERIA: THE RIVERS STATE EXPERIENCE - Christopher Barisi Barigbon; Tambari Adooh; Barikuma Lazarus Ndaage (PT. Antis International Publisher, 2026)
Objective: This paper examines a new trend in Nigerian politics that is defined by the increasing power of elite players who operate outside of official party lines. The paper examines how political players maintain their relevance in the face of rival party formations, the institutional framework that permits this kind of dual positioning, and the consequences of these dynamics for Nigerian democratic governance, party ideology, and accountability. Method: The study uses a qualitative and descriptive research design based on media reports, documentary sources, and previously published literature on Nigerian party politics. It is grounded in elite theory and patron-client theory. Results: The results show that through elite broking, institutional penetration, patronage networks, electoral coordination, and discursive control over political narratives, dominant political actors have been able to simultaneously influence both ruling and opposition parties due to weak party institutions, patronage-driven politics, and the personalisation of power. Novelty: The paper conceptualizes